2019
DOI: 10.1097/bot.0000000000001337
|View full text |Cite|
|
Sign up to set email alerts
|

Knee Pain and Functional Scores After Intramedullary Nailing of Tibial Shaft Fractures Using a Suprapatellar Approach

Abstract: Objectives: To evaluate the effects of intramedullar nailing of the tibia using a suprapatellar (SP) approach with respect to pain and function of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
3
16
1
1
Order By: Relevance
“…In the present study, patients in the subperiosteal cocktail injection group felt less pain at the first day after TKA. This result was in line with our assumption above [32]. Cocktails could directly act on the subperiosteal nerves and might bring better analgesia effects.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, patients in the subperiosteal cocktail injection group felt less pain at the first day after TKA. This result was in line with our assumption above [32]. Cocktails could directly act on the subperiosteal nerves and might bring better analgesia effects.…”
Section: Discussionsupporting
confidence: 91%
“…In the majority of the studies, the infrapatellar approach was described [4,[7][8][9]). Six studies reported on the suprapatellar approach [4,5,[7][8][9][79][80][81][82][83] and one on the semi-extended technique [66]. There were 17 randomized trials [7, 9, 19, 23, 26, 30, 48, 49, 52, 54, 57, 59-61, 64, 68, 71] of which five compared different methods for tibial nailing [7,9,26,49,71], 14 prospective studies [5,11,14,28,31,34,37,39,46,55,70,72,73,83] and 45 retrospective studies [4, 8, 12, 13, 15-18, 20-22, 24, 25, 27, 29, 32, 33, 35, 36, 38, 40-45, 47, 50, 51, 53, 56, 58, 62, 63, 66, 67, 69, 74, 76, 78-82, 84].…”
Section: Resultsmentioning
confidence: 99%
“…The Short Form-36 (SF-36)[5,7,9,24,43,48,51,61,67,80,83], SF-12[4], EQ5D[60], and the Nottingham Health Profile[23,60] were used to measure quality of life after tibial nailing. The pooled estimates could only ) for the suprapatellar technique (Fig.6a, b).…”
mentioning
confidence: 99%
“…In the management of tibial shaft fractures, intramedullary nailing is the treatment of choice. 11 Low percentage of complications like non-union, infection, mal-union, deep venous thrombosis, thermal necrosis and compartment syndrome has been reported following tibial nailing in literature. 12 The most frequent adverse consequence of tibial nailing is chronic anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%